2018
DOI: 10.1128/mbio.00694-18
|View full text |Cite
|
Sign up to set email alerts
|

Four Molybdenum-Dependent Steroid C-25 Hydroxylases: Heterologous Overproduction, Role in Steroid Degradation, and Application for 25-Hydroxyvitamin D 3 Synthesis

Abstract: Side chain-containing steroids are ubiquitous constituents of biological membranes that are persistent to biodegradation. Aerobic, steroid-degrading bacteria employ oxygenases for isoprenoid side chain and tetracyclic steran ring cleavage. In contrast, a Mo-containing steroid C-25 dehydrogenase (S25DH) of the dimethyl sulfoxide (DMSO) reductase family catalyzes the oxygen-independent hydroxylation of tertiary C-25 in the anaerobic, cholesterol-degrading bacterium Sterolibacterium denitrificans. Its genome cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…denitrificans harbors eight alpha subunits (molybdopterin-containing subunits) of C25DH, and the substrate specificity of each subunit (S25dA1–8) has been studied through proteome analysis ( 14 ). We identified homologues of S25dA1–A7, but the expression level of S25dA1 homologues in our cholesterol-treated sludge was highest; this is congruent with previous studies that indicated that S25dA1 is responsible for the side chain hydroxylation of cholest-4-en-3-one due to its high substrate specificity ( 14 , 36 ). Interestingly, our maximum likelihood tree clearly separated subunits with side chain specificity (S25dA1–4) and subunits without specificity (S25dA5–A7) into two lineages and grouped homologues of each subunit into distinct clades (except S25dA2).…”
Section: Discussionsupporting
confidence: 92%
“…denitrificans harbors eight alpha subunits (molybdopterin-containing subunits) of C25DH, and the substrate specificity of each subunit (S25dA1–8) has been studied through proteome analysis ( 14 ). We identified homologues of S25dA1–A7, but the expression level of S25dA1 homologues in our cholesterol-treated sludge was highest; this is congruent with previous studies that indicated that S25dA1 is responsible for the side chain hydroxylation of cholest-4-en-3-one due to its high substrate specificity ( 14 , 36 ). Interestingly, our maximum likelihood tree clearly separated subunits with side chain specificity (S25dA1–4) and subunits without specificity (S25dA5–A7) into two lineages and grouped homologues of each subunit into distinct clades (except S25dA2).…”
Section: Discussionsupporting
confidence: 92%
“…Based on genomics and metabolomics studies, S. denitrificans appeared to utilize a range of steroid C25 dehydrogenases for oxygen-independent C25-hydroxylations of steroids with different isoprenoid side chains, followed by an unusual conversion to C26-oic acids (Warnke et al 2017 ). This hypothesis was very recently confirmed by successful heterologous overexpression of paralogous S25DH-like genes in Thauera aromatica K172 and characterization of substrate specificity for four different enzymes (Jacoby et al 2018 ). After complete degradation of the aliphatic side chain, androst-4-en-3,17-dione (AD) and/or androst-1,4-dien-3,17-dione (ADD) enter the central degradation pathway via 2,3- seco -AB-rings opening (Chiang and Wael 2011 ; Wang et al 2013 ; Wang et al 2014 ).…”
Section: Introductionmentioning
confidence: 78%
“…This hypothesis was very recently confirmed by successful production of recombinant S25DH isoenzymes (S25DH 1–4 ) in T. aromatica K172 and Azoarcus sp. CIB and characterization of substrate specificity for individual enzymes (see below and Jacoby et al 2018 ). The attempts to obtain overexpress S25DH enzymes in E. coli systems yielded either non or trace activity only (Jacoby et al 2018 ; Rugor et al 2017b ).…”
Section: O 2 -Independent Hydroxylationmentioning
confidence: 99%
See 2 more Smart Citations